Laser-Induced Nanowire Percolation Interlocking for Ultrarobust Soft Electronics - Yeongju Jung; Kyung Rok Pyun; Sejong Yu; Jiyong Ahn; Jinsol Kim; Jung Jae Park; Min Jae Lee; Byunghong Lee; Daeyeon Won; Junhyuk Bang; Seung Hwan Ko (Nano-Micro Letters)
Highlights Laser-induced percolation interlocking technology enables the development of the robust, open-structured nanowire (NW) electrodes through the photothermal effect at the interface between NW and substrate. The optimized NW electrode with enhanced mechanical and electrical properties can be used as reusable wearable electronics. Stable functionalization of the percolation-interlocked NW electrode with various conducting polymers can be achieved, broadening the applicability as soft electronics.